2020
DOI: 10.1080/00016357.2020.1739330
|View full text |Cite
|
Sign up to set email alerts
|

Do enamel and dentine caries at 5 years of age predict caries development in newly erupted teeth? A prospective longitudinal study

Abstract: Objective: To explore caries development in children from 5 to 12 years of age, and to study whether enamel caries and dentine caries at 5 years of age could predict caries prevalence at 12 years of age, controlled for child characteristics. Methods: The study included 3282 children examined at 5 and 12 years of age. Data were collected by clinical examination and questionnaire. Enamel and dentine caries were registered at surface level. Data were tested by t-test and analysed by bi-and multivariate logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…A total of 32 articles were retrieved for full text reading and evaluation. Ten articles were found to be eligible and included for qualitative synthesis [ 8 , 9 , 10 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] (Kappa κ: 0.899). The list of excluded studies and the reasons for exclusion are shown in Supplementary Material File S2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 32 articles were retrieved for full text reading and evaluation. Ten articles were found to be eligible and included for qualitative synthesis [ 8 , 9 , 10 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] (Kappa κ: 0.899). The list of excluded studies and the reasons for exclusion are shown in Supplementary Material File S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Nine prospective and one retrospective studies were included, with 7580 children ranging from 1.5 years old to 5 years old at baseline with primary dentition, and followed up until 6 to 14 years old in mixed dentition [ 8 , 9 , 10 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The duration of follow-up ranged from 3 to 12 years with 6786 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, the oral cavity is a dynamic environment with several transitions between the various dentition stages (primary, mixed, and permanent) [5]. Oral health or disease between these stages are strongly correlated, as caries experience in primary teeth often influences the caries outcome in permanent dentition [6]. The caries experience in primary posterior teeth has been established as a reliable predictor for the subsequent decay Microorganisms 2022, 10, 1129 2 of 12 in permanent dentition [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…ECC is considered severe when it affects children under 3 years of age (American Academy of Pediatric Dentistry, 2019a ). ECC is one of the most prevalent health problems worldwide; it affects more than 500 million children and entails the risk of suffering multiple episodes of pain and oral infections, and may even affect permanent dentition (GBD 2015 Disease and Injury Incidence and Prevalent Collaborators, 2016 ; Kassebaum et al, 2017 ; Li & Wang, 2002 ; Saethre‐Sundli et al, 2020 ). Patient cooperation at these early ages may be poor, and the difficulty of managing these patients generates an increase in the demand for care at the hospital level (American Academy of Pediatric Dentistry, 2019b ).…”
Section: Introductionmentioning
confidence: 99%